Model for supply chain management to support organizational control - Kokkonen, Juho (My University, 2005)
The primary objective of this research was to construct model that supports organizational control in a supply chain and test the usefulness of the model in practice. Research method was a constructive-case study. Theoretical component of construction is based on the supply chain management philosophy and the organizational control. Theoretical part of supply chain management presents the special characteristics, which influence supply chain control. Secondly, theory presents the requirements of organizational control and significance of information’s in a control. The research data was collected by methods, which have been recommended to be use in a case-study. The Open-ended interviews and survey were produced before construction process. The purpose of results was to give a practical view for the construction. Before model construction, 22 people representing internal supply chain were interviewed and the 62 people of external supply chain surveyed. The respondents included staff from managerial and operational levels. After the final form of the model had been created the validity of research checked and confirmed with additional. The results of this research present a detailed model for sales and marketing organisations control in a volume-intensive supply chain. The model integrates the performance measurement and situational supply chain information as a part of the organisational control in a supply chain. The measures and way to present information for the sales and marketing organisations control are presented in a detailed model. The model was tested and mobilized in a case-company. The tested model is also presented in a simplified form. The simplified model presents an example of, how organisational control can be exercised in a supply chain.
Keywords: Supply Chain Management; performance measurement; organizational control; information; constructive approach; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|